Rugose spiraling whitefly Aleurodicus rugioperculatus Martin (Hemiptera: Aleyrodidae) - Vivek Kumar; Cindy L. McKenzie; Catharine Mannion; Ian Stocks; Trevor Smith; Lance S. Osborne (EDIS, 2013)
A new addition on the list of whitefly species found in Florida, Aleurodicus rugioperculatus Martin, was originally called the gumbo limbo spiraling whitefly, but is now named the rugose spiraling whitefly. Being a fairly new species to science – identified less than a decade ago, not much information is available about this pest. It is an introduced pest, endemic to Central America, and was reported for the first time in Florida from Miami-Dade County in 2009. Since then it has become an escalating problem for homeowners, landscapers, businesses, and governmental officials throughout the southern coastal counties of Florida. Feeding by this pest not only causes stress to its host plant, but the excessive production of wax and honeydew creates an enormous nuisance in infested areas. The presence of honeydew results in the growth of fungi called sooty mold, which then turns everything in the vicinity covered with honeydew black with mold. This 5-page fact sheet was written by Vivek Kumar, Cindy L. McKenzie, Catharine Mannion, Ian Stocks, Trevor Smith, and Lance S. Osborne, and published by the UF Department of Entomology and Nematology, October 2013. http://edis.ifas.ufl.edu/in1015